2016
DOI: 10.20853/30-5-593
|View full text |Cite
|
Sign up to set email alerts
|

Exploring student engagegment practises at a South African university: Student engagement as reliable predictor of academic performance

Abstract: Student engagement is one avenue to explore how the experiences within and beyond the classroom impact student persistence behaviours. This article contributes to the sparse research in South Africa on the correlates of student engagement with academic performance at a Historically Disadvantaged University. The results suggest that engagement practices at this university differ across race and gender and that given the South African history we are able to generalise onto the South African higher education syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 7 publications
3
34
0
Order By: Relevance
“…Students not only develop their content knowledge through these behaviours, but also demonstrate that they are engaging with course material (Nagaoka et al 2013). Schreiber and Yu (2016) found a significant and positive relationship between student engagement and academic performance.…”
Section: Academic Behavioursmentioning
confidence: 87%
“…Students not only develop their content knowledge through these behaviours, but also demonstrate that they are engaging with course material (Nagaoka et al 2013). Schreiber and Yu (2016) found a significant and positive relationship between student engagement and academic performance.…”
Section: Academic Behavioursmentioning
confidence: 87%
“…The differential effect of race and gender on student outcomes has been widely explored in the literature (Bhorat, Goga and Stanwix, 2014;Gross, Torres and Zerquera, 2013;Kim, 2004;Kim and Sax, 2014;Schreiber and Yu, 2016). The effect of financial aid can be moderated by race and ethnicity (Gross, Torres and Zerquera, 2013).…”
Section: Race and Gendermentioning
confidence: 99%
“…Recent research conducted on student engagement at the UWC has also highlighted a number of factors which play a role in student engagement. Schreiber and Yu's (2016) study examining student engagement at the University of the Western Cape (UWC) found that engagement patterns are different across race and gender while highly correlated to academic performance. The authors were able to generalise these results onto the South African higher education system (Schreiber & Yu, 2016).…”
Section: The Case Of the University Of The Western Capementioning
confidence: 99%
“…Schreiber and Yu's (2016) study examining student engagement at the University of the Western Cape (UWC) found that engagement patterns are different across race and gender while highly correlated to academic performance. The authors were able to generalise these results onto the South African higher education system (Schreiber & Yu, 2016). Like other South African universities, UWC has also struggled with student retention and throughput.…”
Section: The Case Of the University Of The Western Capementioning
confidence: 99%